2023
DOI: 10.7759/cureus.36854
|View full text |Cite
|
Sign up to set email alerts
|

Osteopathic Manipulation as a Method of Cortisol Modification: A Systematic Review

Abstract: The effectiveness of osteopathic manipulative treatment (OMT) in the modification of various hormones has been studied; however, there is still a need for quantitative measurements to determine how large of an influence exists. The goal of this meta-analysis is to investigate the implications OMT has on cortisol levels. A systematic literature search restricted to English was performed from October 2022 to November 2022 using Google Scholar, OSTMED.DR, and PubMed and included articles from 2000 onward. Article… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Inclusion criteria were male gender and being a fire academy cadet. The exclusion criteria were daily cigarette smoking, alcohol abuse, caffeine use (>300 mg/day), medication, drug use, reported medical illness, and the following types of disorders: endocrine, cardiovascular disease, and psychiatric, physiotherapeutic or osteopathic therapy applied now or in the past, because therapeutic intervention involving, for example, spinal manipulation increases cortisol levels in the body [16,17]. In this study, we were keen to exclude factors that may affect stress hormones.…”
Section: Participantsmentioning
confidence: 99%
“…Inclusion criteria were male gender and being a fire academy cadet. The exclusion criteria were daily cigarette smoking, alcohol abuse, caffeine use (>300 mg/day), medication, drug use, reported medical illness, and the following types of disorders: endocrine, cardiovascular disease, and psychiatric, physiotherapeutic or osteopathic therapy applied now or in the past, because therapeutic intervention involving, for example, spinal manipulation increases cortisol levels in the body [16,17]. In this study, we were keen to exclude factors that may affect stress hormones.…”
Section: Participantsmentioning
confidence: 99%
“…Similarly, MBIs were shown to improve HRV by decreasing LF and LF/HF and increasing HF, SDNN, and RMSSD in some reviews (after mindfulness, yoga, and/or tai chi) [54,56], while others showed no changes in LF, HF, LF/HF, RMSSD, and SDNN (after mindfulness) [57]. Nonetheless, the literature on the effect of OMT and MBI on stress and cortisol levels as well as autonomic activity and HRV remains partially limited and heterogenous, and future research is needed [35,36,54,58]. Taken together, OMT and MBI were shown to reduce stress (by means of decreased cortisol levels) and enhance autonomic activity (by means of increased HRV) [35,37,54,58].…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, OMT was shown to improve stress and cortisol levels in some studies [30,31] but not others [32][33][34]. A recent systematic review concluded that OMT decreases cortisol levels with a medium effect [35]. Similarly, reviews have shown that OMT improves autonomic activity [36,37] and HRV [38,39].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation